Dystrophic Adipocytes Mimicking Metastatic Signet Ring Cell Adenocarcinoma: A Diagnostic Pitfall in a Cachectic Patient. (7th May 2018) - Zhang, Xin; Findeis-Hosey, Jennifer J.
Abstract : Cachexia is a debilitating condition and complex syndrome commonly associated with a variety of chronic diseases. It is caused by metabolic dysregulation and characterized by profound loss of adipose tissue and skeletal muscles. While pathological changes of cachectic conditions on adipose tissue have been studied and documented in tumor-bearing animal models, similar morphological changes in human surgical specimens are rare. Here we report a case of a cachectic patient with pancreatic adenocarcinoma whose adipocytes underwent dramatic lipodystrophy mimicking signet ring cell adenocarcinoma. The patient had presented with a large bowel obstruction, a mass extending between the pancreas and colon, and radiographic concern for carcinomatosis. A moderately differentiated adenocarcinoma was identified invading externally into the colon, with extensive signet ring-like cells throughout the specimen, including those adjacent to the colon and lymph nodes and around nerves. These signet ring-like cells were round with variably clear to eosinophilic cytoplasm and a peripherally displaced round to oval nucleus. Immunohistochemical staining demonstrated that these signet ring-like cells were negative for AE1/AE3, CD138, or Kreyberg staining, while they were positive for S-100 staining, confirming these as dystrophic adipocytes. Here we examine dystrophic adipocytes in a cachetic patient, examining the differential diagnosis and potential ancillary studies.